Volatile oils from Philodendron meridionale Buturi & Sakur: chemical composition and in vitro effect against Ctenocephalides felis and leukemia cells (Research, Society and Development, 2021)
Essential oils are an important natural source of pesticides and can be suitable used in ectoparasite control. The goal of this paper was to investigate the chemical composition of the volatile oils obtained from leaves and stems of Philodendron meridionale Buturi & Sakur by gas chromatography/mass spectrometry and to evaluate their insecticidal effect against Ctenocephalides felis Bouché adult insects and their cytotoxicity on human Jurkat leukemic T-cells by 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazoluim bromide (MTT) reduction method. The main compound was ent-kaur-16-ene at concentrations of 20.78 and 22.46% for volatile oils from leaves and stems, respectively. These volatile oils provided insecticidal effect against C. felis with an average knockdown time of 9.61 and 7.35 min for fumigant test performed with the leaves and stems samples, respectively. Considering the topical application, these P. meridionale volatile oils extracted from leaves and stems demonstrated average knockdown values of 14.70 and 20.0 min, respectively. A very low cytotoxic effect of 9.48 and 11.32% was observed for P. meridionale volatile oils from leaves and stems even at the highest tested concentration of 400 μg.mL-1, respectively. Therefore, it is possible to propose a biological selectivity to the volatile oils under study, which guarantees, at the same time, effect against this insect with no evident damage to human biological system.